PENGARUH HARGA, KEPERCAYAAN, BRAND LOVE DAN E-PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH PADA PENGGUNA APLIKASI TIKTOK PADA ERA PANDEMI COVID 19 - Elisabet Krida Juli (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
The Covid-19 pandemic that has hit the world today has had a profound impact on economic development and changes in human behavior in meeting needs, both primary and secondary. Changes in consumer behavior in making purchasing decisions greatly affect online shopping purchasing patterns during the prepandemic and post-pandemic periods. Local products that dominate the market share are Wardah Cosmetics, with the image as halal cosmetics, Wardah cosmetic products are in great demand. Data processing is done computerized using several statistical data processing software, namely Statistical Product and Services Solution (SPSS). The study was conducted on Wardah's followers on the TikTok application with a sample of 100 respondents, where the sample was selected using a random sampling method. Based on data analysis using multiple linear regression analysis. The results of the study can be stated that the advertising variable has a significant positive effect on purchasing decisions, the trust variable has a significant positive effect on purchasing decisions, the e-promotion variable has a significant positive effect on purchasing decisions, while the brand love variable has no significant effect on purchasing decisions for Wardah products on Tiktok application users. the era of the Covid-19 pandemic.